1989
DOI: 10.1111/j.1467-9817.1989.tb00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Phonemic Analysis: effects of word properties

Abstract: A BS TRA CTThe relation between performance in phonemic segmentation and reading and writing ability is discussed. Not much is known about how segmentation is carried out and which word properties influence performance. Therefore, effects of word properties (length, CV structure, syllabic structure, meaning) were investigated in two experiments. Strong indications were obtained that an onset-rime distinction is relevant for the process of segmentation. The meaning of a word appears to have no influence. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
5

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 29 publications
5
38
1
5
Order By: Relevance
“…In addition to these differences between tasks, differences in linguistic complexity within tasks appear to influence phonological awareness (Anthony & Francis, 2005). For example, according to Schreuder and van Bon (1989) the consonantvowel (CV) structure is an important determinant. Therefore, as a next step, we have investigated the differences in difficulty of various CV structures.…”
Section: The Present Studymentioning
confidence: 99%
“…In addition to these differences between tasks, differences in linguistic complexity within tasks appear to influence phonological awareness (Anthony & Francis, 2005). For example, according to Schreuder and van Bon (1989) the consonantvowel (CV) structure is an important determinant. Therefore, as a next step, we have investigated the differences in difficulty of various CV structures.…”
Section: The Present Studymentioning
confidence: 99%
“…Thus, it may be more difficult for children to segment the first consonant of the word "tray," because /t/ is part of the onset /tr/, than to segment /r/ from /ay/, because /r/ belongs to the onset and /ay/ belongs to the coda. Schreuder and Van Bon (1989) found that children performed better on stimuli that do not begin with consonant clusters (i.e., consonant (C)/vowel (V) combination, e.g., "vaa" [CV, consonant, vowel]) than on stimuli that begin with these clusters (e.g., "bra" [CCV]). …”
Section: Word Propertiesmentioning
confidence: 99%
“…However, nasal blends (like /nk/, /nd/ and /mp/) and liquid blends (/ld/) in the coda seemed easier to segment. Schreuder and Van Bon (1989) showed that consonant clusters in the coda are more difficult to segment than vowelconsonant combinations. Children performed better when stimuli end with a vowel-consonant combination (VC, e.g., "aag") than a consonant cluster (VCC, e.g., "urg").…”
Section: Word Propertiesmentioning
confidence: 99%
See 2 more Smart Citations